ACLIMATAR: Climate adaptation planning tool for cocoa, coffee and tea farming - Schmidt, Paul G.; Castro-Llanos, Fabio; Gutierrez, Natalia; Bunn, Christian (2023)
To facilitate decision making, climate projection data needs to be localised and presented in an accessible interface. The ACLIMATAR tool provides access to localized data on climate change and future projections for major cocoa, coffee, and tea growing regions. The tool is structured into three main parts: Climate data view, Map view and Solution space. The climate data view provides information on changes in precipitation and temperature, as well as specific climate hazards to be expected. In the Map view, a map interface displays changes in the distribution of agro-climatic zones in your region, while the impact gradient indicates the severity of expected changes. The solution space provides prioritised recommendations for climate adaptation, as well as differentiated recommendations based on your climate adaptation zone. The tool is beneficial for field extensionists who are planning field activities related to climate change, as well as higher-level decision-makers and anyone working on cocoa, coffee or tea.